Effect of humidity and counterface material on the friction and wear of carbon fiber reinforced PTFE composites. (May 2021) - Johansson, Pontus; Marklund, Pär; Björling, Marcus; Shi, Yijun
Abstract: The tribological performance of PTFE composites is affected by both the composition of the counterface material and the sliding environment. However, no comprehensive investigation has been conducted on the combined effect of the humidity and counterface material on PTFE composites. This study investigates the tribological behavior of carbon fiber reinforced PTFE composites sliding in a dry nitrogen environment at different humidity levels. Experiments were conducted in an enclosed tri-pin-on-disc tribometer against two different metallic counterface materials. Tests in laboratory air were used for comparison. Results indicate that the tribological performance of carbon fiber reinforced PTFE composites are sensitive to environmental changes. The impact of humidity on both the coefficient of friction and specific wear rate was up to about 40%. Highlights: Humidity affects the sliding wear of carbon fiber reinforced PTFE composites. Counterface material alters the effect of humidity. Counterface material greatly affects the friction of PTFE composites. Significant increase in friction and wear when changing the sliding environment from nitrogen to laboratory air. Graphite is not extruded from ductile cast iron due to sliding of PTFE composites.